A suggestion to radiological hazards characterization of 226Ra, 232Th, 40K and 137Cs: spatial distribution modelling - Akozcan, Serpil; Kulahci, Fatih; Mercan, Yeliz (Elsevier Science Bv, 2018)
Spatial distribution modelling has been proposed to characterize the radiological hazards associated with concentration of natural Ra-226, Th-232, K-40 and artificial Cs-137 radionuclides in the nature. These elements have been determined for the sediment samples of the Bafa Lake with the aim of radiation hazard evaluation via a high purity germanium detector gamma spectrometry. Their activity concentrations in sediments are in the ranges of 29.87 +/- 2.2-72.56 +/- 11 Bq kg(-1) dry weight (dw), 31.57 +/- 3.5-66.48 +/- 8.3 Bq kg(-1) (dw), 332.01 +/- 12-1092.37 +/- 21 and 0.65 +/- 0.04-3.96 +/- 0.78 Bq kg(-1)(dw), respectively. In order to determine the radiological hazard associated with the radioactivity in the samples, the external terrestrial gamma dose rate in air, annual effective dose rate, the radium equivalent activity and the external hazard index are calculated and compared with the data from literature. Moreover, the spatial modelling distributions are obtained visually for radiological hazards characterization of these elements, which are very dangerous in terms of radiological and environmental pollution in the nature. These visual distributions give meaningful information for future researches on the migration of radionuclides in the environment.
Keywords: Radiological hazard; Spatial distribution; Risk assessment; Kriging; Radionuclides